2004
DOI: 10.1046/j.0954-6820.2003.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's lymphoma, Epstein–Barr virus reactivation and fatal haemophagocytic syndrome

Abstract: Haemophagocytic syndrome is a serious disorder, often related to Epstein-Barr virus (EBV) or other infectious agents. Frequently an underlying immune abnormality or a T-cell lymphoma is present. The combination of haemophagocytosis and Hodgkin's lymphoma seems to be rare. A 70-yearold female with rheumatoid arthritis was admitted with constitutional symptoms, persistent fever, pancytopenia, deranged liver enzymes, lymphadenopathy and splenomegaly. A fatal coagulopathy supervened. The clinical picture and the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 59 publications
1
16
0
1
Order By: Relevance
“…Those reports revealed that the mixed cellularity type and lymphocytedepleted type are two major types of Hodgkin lymphoma that accompany HLH. In addition, most cases showed Epstein-Barr virus to be present in the Hodgkin cells or Reed-Sternberg cells (4,5,10). Consistent with these findings, the pathological diagnosis of our patient was the mixed cellularity type in which Reed-Sternberg cells were positive for EBER1 staining.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Those reports revealed that the mixed cellularity type and lymphocytedepleted type are two major types of Hodgkin lymphoma that accompany HLH. In addition, most cases showed Epstein-Barr virus to be present in the Hodgkin cells or Reed-Sternberg cells (4,5,10). Consistent with these findings, the pathological diagnosis of our patient was the mixed cellularity type in which Reed-Sternberg cells were positive for EBER1 staining.…”
Section: Discussionsupporting
confidence: 74%
“…Hodgkin lymphoma-associated HLH is rare with only a limited number of reported cases (3)(4)(5). Those reports revealed that the mixed cellularity type and lymphocytedepleted type are two major types of Hodgkin lymphoma that accompany HLH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these subtypes have significantly unfavorable prognoses in Western countries, as well as in Asia (15). In the past, the majority of patients with HLHassociated HL were observed to have the LD or MC subtype (11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). These findings raise the possibility that EBV plays a key role in the pathogenesis of HLH.…”
Section: Introductionmentioning
confidence: 64%
“…In 1981, a case of T-cell lymphoma resembling MH was reported (Kadin, 1981). Following this report, many lymphoma cases associated with HPS have been reported worldwide (Han et al, 2007;Hasselblom et al, 2004;Ishii et al, 2007;Janka et al, 1998;Reiner & Spivak, 1988;Tong et al, 2008). In most of these cases it was proven that the proliferating cells were not of histiocytic origin, but that they were lymphoma cells.…”
Section: Historical Background and Terminology Of Hlhmentioning
confidence: 99%